2009
DOI: 10.1080/08977190802587049
|View full text |Cite
|
Sign up to set email alerts
|

The levels of vascular endothelial growth factor-A and placental growth factor-2 in embryopathy associated with experimental diabetic gestation

Abstract: The objective of this study was to investigate the role of vascular endothelial growth factor-A (VEGF-A) and placental growth factor-2 (PlGF-2) in fetal malformations associated with maternal diabetes. Diabetes was induced in female rats. Diabetic and control female rats were made pregnant. On Day 15 of gestation, rats were sacrificed and embryos and their placentas and membranes were dissected out of the uterine horns. Following morphological examination, embryos and their placentas and membranes were homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
2
0
1
Order By: Relevance
“…In addition to the parameters of oxidative stress and anti-oxidant measured, we also measured the activity of various enzymes and growth factors in placenta. Our results are in concordance with previous studies that demonstrated association of sFlt-1 elevation with diabetes or pre-eclampsia (Salim et al 2009 ; Wu et al 2010 ). Given the known functions of PIGF-2 and sFlt-1, we can hypothesize that the observed pattern reflect an abnormality in the fetal or placental vasculature.…”
Section: Discussionsupporting
confidence: 94%
“…In addition to the parameters of oxidative stress and anti-oxidant measured, we also measured the activity of various enzymes and growth factors in placenta. Our results are in concordance with previous studies that demonstrated association of sFlt-1 elevation with diabetes or pre-eclampsia (Salim et al 2009 ; Wu et al 2010 ). Given the known functions of PIGF-2 and sFlt-1, we can hypothesize that the observed pattern reflect an abnormality in the fetal or placental vasculature.…”
Section: Discussionsupporting
confidence: 94%
“…In fetuses from streptozotocin-induced diabetic mice, impaired methylation and expression of the imprinted genes H19 and IGF-II have been found related to the microsomic phenotype (245). Levels of angiogenic factors like vascular endothelial growth factor-A and placental growth factor-2 are reduced in fetuses smaller in weight from streptozotocin-induced diabetic rats (171).…”
Section: Fetal Growthmentioning
confidence: 94%
“…Aberrant concentrations of several prostaglandins that regulate the balance between proinflammatory/antiinflammatory pathways and between vascular relaxation/ dilation are found in placentas from streptozotocin-induced diabetic rats and ewes (56, 151, 170). On the other hand, enhanced vascularization and increased angiogenic factors like vascular endothelial growth factor and placental growth factor are found in placentas from streptozotocin-induced diabetic rodents (153,171,172).…”
Section: B the Placentamentioning
confidence: 99%
“…Sob a influência de fatores angiogênicos, células angiogênicas e trofoblásticas migram através da MEC esculpindo a rede vascular da placenta, que é essencial para sua fisiologia (124,125). Além das alterações da MEC, da expressão de fatores antigênicos e de seus receptores, alterações vasculares da placenta foram relatadas em placentas diabéticas (106,123,126,127). O papel fundamental dos fatores angiogênicos, componentes da MEC e MMPs na angiogênese, permite-nos sugerir que distúrbios simultâneos sobre esses fatores ocasionados pelo diabetes têm potencial para prejudicar a formação do labirinto, bem como suas funções.…”
Section: Matriz Extracelularunclassified